Study of Reaction Mechanisms in α + 69Ga reaction at ≈10 – 50 MeV - F. K. Amanuel (East African Journal of Biophysical and Computational Sciences)
The excitation functions of 69Ga(α, n)72As, 69Ga(α, 2n)71As, 69Ga(α, 3n)70As, 69Ga(α, x)69Ge, 69Ga(α, x)68Ga and 69Ga(α, x)67Ga reactions produced in the interaction of α-projectile with 69Ga-target were studied at ≈ 10-50 MeV. The produced nuclei were different isotopes of As, Ge, and Ga, some of which have important medical applications. The theoretical model predictions were based on the statistical code COMPLETE, and the predicted results were compared and discussed with existing experimental data. Good agreement between the theoretical predictions and experimental results were obtained. Pearson's relational statistics showed moderate to strong positive correlations between the theoretically predicted and experimentally measured reaction cross-sections. Furthermore, the present investigation revealed significant pre-compound contributions in the studied energy range. Therefore, it is important to consider the admixture of pre-equilibrium and equilibrium modes of reactions when predicting the reaction cross-sections.